Quantifying the impact of climate and vegetation changes on runoff based on the budyko framework in the Lake Issyk-Kul Basin, Kyrgyzstan - Feng, Pingping; Alifujiang, Yilinuer; Abuduwaili, Jilili; Lu, Na; Jiang, Ying (Frontiers in Earth Science, 2023)
Identifying and quantifying the drivers of runoff (R) variability is fundamental to our understanding of the hydrologic cycle and necessary for decision makers to manage water resources. Climate variables and vegetation are the main factors influencing the R. However, the effects of climate and vegetation changes on R are still poorly understood, especially in arid regions with limited water resources. This study quantifies the contribution of precipitation (PRE), potential evapotranspiration (ET0), and Normalized Difference Vegetation Index (NDVI) to R in Lake Issyk-Kul Basin (LIKB) dryland Central Asia by using the Budyko model. The results showed that R, PRE, and ET0 decreased from 2000 to 2020, while the NDVI and underlying parameter (ω) showed a slightly increasing trend. By using the Mann-Kendall (M-K) statistical approach, divided the R series into a baseline period (2000–2010) and a change period (2011–2020) based on the breakthrough point (2011). In the baseline period, R showed a decreasing trend, while in the change period, R showed an increasing trend of 1.8 mm/yr. The sensitivity analysis shows that a 1 mm increase in PRE results in a 0.48 mm increase in R (sensitivity coefficient to R is 0.48). Conversely, a 1 mm increase in ET0 (sensitivity coefficient to R of −0.03) and a 1 unit increase in NDVI (sensitivity coefficient to R of −343.31) lead to R decreasing by 0.03 and 343.31 mm, respectively. The relative contributions of PRE, ET0 and NDVI were 33.98%, −3.17% and 3.67%, respectively, suggesting that changes in PRE and NDVI contributed to the decrease in R while the opposite for ET0. PRE dominated the decrease in R, which decreased by 26.58 mm, leading to a decrease in R of 12.76 mm. A decrease of 65.33 mm in ET0 and an increase of 0.003 in NDVI resulted in an increase and decrease of 1.96 and 1.18 mm in R, respectively. This study enhances the understanding of the response of the water cycle to climate and vegetation changes in arid regions and can provide theoretical support for water resource management and ecological restoration.